Three-dimensional network structure of silicon-graphene-polyaniline composites as high performance anodes for Lithium-ion batteries. (1st February 2016) - Mi, Hongwei; Li, Fang; He, Chuanxin; Chai, Xiaoyan; Zhang, Qianling; Li, Cuihua; Li, Yongliang; Liu, Jianhong
Graphical abstract: Highlights: 3D network structure of silicon-graphene-polyaniline composite is prepared. The polyaniline layer is bounded graphene-grafted Si through π-π conjugation. The final product shows excellent electrochemical properties with dual protection. Abstracts: Silicon (Si) is regarded as one of the most promising anode materials for Li-ion batteries due to its high theoretical specific capacity (4200 mAh g −1 ). To overcome the poor cycling stability issue associated with its low conductivity and large volume changes (∼300%) during charge/discharge processes, a novel approach to fabricate three-dimensional (3D) network structure of silicon-graphene-polyaniline (Si-G-PANI) has been developed. During this synthetic, the graphene sheet was first coated on the surface of Si from a pyrolysis reaction of the liquid-polyacrylonitrile (LPAN), which not only improves conductivity but also constrains the serious mechanical stress caused by the volume expansion of Si. Subsequently, Si-G-PANI composite was obtained through an in-situ polymerization, the PANI layer is tightly bounded to graphene owing to an enhancement of π conjugation between the PANI and graphene-grafted Si nanoparticles. Herein, PANI layer offers a 3D conductive and protective network to allow the volume variation of Si during cycling, as well as facilitate the electron and lithium ion transfer processes. With the dual protection of graphene and PANI, the Si-G-PANI electrode can deliver a reversible specific capacity of 1001.8 mAh·g −1 at a current density of 1.5 A g −1 after 50 cycles.